2021
DOI: 10.1002/iid3.579
|View full text |Cite
|
Sign up to set email alerts
|

Effect of inactivated nature‐derived microbial composition on mouse immune system

Abstract: Introduction:The hygiene hypothesis suggests that decrease in early life infections due to increased societal-level hygiene standards subjects one to allergic and autoimmune diseases. In this report, we have studied the effect of sterilized forest soil and plant-based material on mouse immune system and gut microbiome.Methods: Inbred C57Bl/6 mice maintained in normal sterile environment were subjected to autoclaved forest soil-derived powder in their bedding for 1 h a day for 3 weeks. Immune response was measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 66 publications
1
25
0
Order By: Relevance
“…We hypothesize that this finding is also relevant for human health. Exposure to highly diverse environmental microbiota can shape commensal microbiota and consequently promote immune modulation [8,43]. In terms of the gut microbiota, microorganisms associated with fresh produce, including fruits, constitute an important exposome.…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesize that this finding is also relevant for human health. Exposure to highly diverse environmental microbiota can shape commensal microbiota and consequently promote immune modulation [8,43]. In terms of the gut microbiota, microorganisms associated with fresh produce, including fruits, constitute an important exposome.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, we have observed in several of our studies that exposure to non-inactivated (live) BDB is safe in children and healthy adults without any reported pathogenicity [20,29]. This was observed in animal studies where exposure to inactivated or even non-inactivated BDB was well tolerated without any adverse health issues [40,59]. Moreover, lipopolysaccharides (LPS), which are the endotoxins that are produced by Proteobacteria are known immunomodulatory molecules [60].…”
Section: Discussionmentioning
confidence: 57%
“…Notably, bacterial endotoxins, including lipopolysaccharides (LPS), that are major antigenic determinants of gram-negative bacteria are resistant to autoclaving and heat treatments [56]. In addition, our previous study revealed that BDB autoclaved at 121°C exhibited immunoregulatory potential in C57BL/6 mice and stabilized the microbiome [40]. However, we here observed that autoclaving at 121°C does not effectively remove all murine pathogens suggesting that autoclaving at 134°C is a better way to sterilize the product.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Soil intake also affected the Treg/Th17 balance, and the expression of anti-inflammatory IL-10 relative to that of IL-5 in the lung was greater in Soil group, which positively improved asthma symptoms although the difference was not significant. González-Rodríguez et al found that exposure to dust derived from sterilized forest soil reduced the levels of IL-17F in serum and TNF-α in splenocytes(40). Similarly, in our study, significant reductions in the serum concentrations of IL-17F and TNF-α were observed after soil ingestion.…”
Section: Discussionmentioning
confidence: 99%